2019
DOI: 10.1002/anie.201902109
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh‐Loading Zinc Single‐Atom Catalyst for Highly Efficient Oxygen Reduction in Both Acidic and Alkaline Media

Abstract: Atomically dispersed Zn–N–C nanomaterials are promising platinum‐free catalysts for the oxygen reduction reaction (ORR). However, the fabrication of Zn–N–C catalysts with a high Zn loading remains a formidable challenge owing to the high volatility of the Zn precursor during high‐temperature annealing. Herein, we report that an atomically dispersed Zn–N–C catalyst with an ultrahigh Zn loading of 9.33 wt % could be successfully prepared by simply adopting a very low annealing rate of 1° min−1. The Zn–N–C cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
342
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(354 citation statements)
references
References 20 publications
11
342
0
1
Order By: Relevance
“…The f‐FeCoNC‐900 exhibited an onset potential of 1.05 V and half‐wave potential of 0.89 V versus RHE, which outperformed the Pt/C catalyst in the alkaline solution. Li et al reported a Zn‐N‐C SAC with a high loading (9.33 wt%) of Zn atomically dispersed in the catalyst. This catalyst exhibited higher ORR activity and better stability than those of Fe‐N‐C catalysts in both acidic and alkaline media.…”
Section: Recent Advances Of Densely Populated Sacs In Catalytic Applimentioning
confidence: 98%
See 1 more Smart Citation
“…The f‐FeCoNC‐900 exhibited an onset potential of 1.05 V and half‐wave potential of 0.89 V versus RHE, which outperformed the Pt/C catalyst in the alkaline solution. Li et al reported a Zn‐N‐C SAC with a high loading (9.33 wt%) of Zn atomically dispersed in the catalyst. This catalyst exhibited higher ORR activity and better stability than those of Fe‐N‐C catalysts in both acidic and alkaline media.…”
Section: Recent Advances Of Densely Populated Sacs In Catalytic Applimentioning
confidence: 98%
“…Generally, there are three key factors that significantly affect the mass loading of single atoms on the support: i) synthesis strategies, ii) precursors, and iii) substrates . For example, zinc single‐atom catalyst with an ultrahigh‐loading of 9.33 wt% has been successfully prepared by strictly controlling the gasification rate of ZnCl 2 precursor under a heating rate of 1 °C min −1 . The as‐obtained catalyst exhibited remarkable electrocatalytic activity and stability for the oxygen reduction reaction (ORR) in both alkaline and acidic solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Adapted with permission. [ 98 ] Copyright 2019, Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim. k) Pt‐based SAC (Pt1‐N/BP) is CO and CH 3 OH resistant, l) but the activity is still worse than the commercial Pt/C in 0.1 m HClO 4 .…”
Section: Molecular Design Of Sacs With Enhanced Orr Activitymentioning
confidence: 99%
“…The observed activity was partially attributed to the highly defective carbon black support containing large amounts of pyridine‐ and pyrrole‐like nitrogen dopants forming several Zn–N x active sites. Another report using Zn as single‐metal catalyst was published in 2019 by the group of Wei . In this occasion, the formation of Zn–N 4 moieties onto a carbon support was carried out by pyrolysis of poly( o ‐phenylenediamine) and ZnCl 2 .…”
Section: Non‐cobalt‐ or Iron‐based Electrocatalystsmentioning
confidence: 99%